Percentage Prevalence of Eimerian Species Composition of Sheep and Goats from Beed District, Maharashtra - S. N. Bhamare and E. L. Jaid, B. V. More*, S. V. Nikam, N. Z. Deshmukh (Recent Research in Science and Technology, 2011)
<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">During the present study ten specimens of Eimeria from sheep and twelve species of Eimeria from goats were encountered. The relative prevalence of the sheep and goats are analysed.